Literature Review : The Role of Games in Nutrition Education for Children in Indonesia (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
Games are one of the media that can be used in nutrition education. Many studies have been conducted to see the effectiveness of games in nutrition education for children. However, no review has been conducted on these studies. This study aims to review various studies that use games in nutrition education. This research is a qualitative research in the form of a literature review. The literature search was conducted online through the Google Scholar database using the keywords education, nutrition, games and children. Initially 40 articles were found, but after adjusting to the inclusion criteria, namely open access, articles published in research or service journals were published for the 2017-2021 period, so that the articles reviewed were 17 articles. The results show that games are used on various topics of nutrition education, such as balanced nutrition, consumption of fruit and vegetables, snacks and breakfast. The types of games used are puzzles, snakes and ladders, nutrition cards, flashcards, quarted, quinted, monopoly, wayang, VEM and guessing pictures. All studies show the effectiveness of games in nutrition education in children. There is no nutrition education that has developed modern games in the form of applications, so in the future it is necessary to conduct studies on this matter to enrich the types of games used in nutrition education.